A perspective of teachers' appropriation of educational innovations. Issue 3 (10th July 2017) - Ng, Wei Sheng Timmy; Wilson, Elaine
Abstract : Purpose: The purpose of this paper is to propose a framework describing teachers' affective and cognitive thought processes, as well as the sensemaking and decision making ongoing within them, during the various stages of the appropriation of an educational innovation. Design/methodology/approach: The Rubicon model of action phases, borrowed from psychology, is first used as a lens to understand teachers' will. The model is subsequently adapted to reconcile it with existing literature on teacher beliefs, teacher sensemaking, and teachers' resistance. Findings: The proposed framework shows that teachers' appropriation of an educational innovation is multi-layered and multi-dimensional. This contradicts appropriation as simply a procedural implementation of research recommendations, culminating in only success or failure. Originality/value: The paper sensitises policymakers, school leaders, and teacher educators to the complexity of the appropriation process. The proposed framework serves as a starting point for school and reform leaders, to re-examine their school's implementation of an educational innovation from a more human relations perspective.